2002
DOI: 10.1890/0012-9658(2002)083[2091:scoama]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Species Co-Occurrence: A Meta-Analysis of J. M. Diamond's Assembly Rules Model

Abstract: J. M. Diamond's assembly rules model predicts that competitive interactions between species lead to nonrandom co-occurrence patterns. We conducted a meta-analysis of 96 published presence-absence matrices and used a realistic ''null model'' to generate patterns expected in the absence of species interactions. Published matrices were highly nonrandom and matched the predictions of Diamond's model: there were fewer species combinations, more checkerboard species pairs, and less co-occurrence in real matrices tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
1,055
6
20

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 885 publications
(1,122 citation statements)
references
References 43 publications
41
1,055
6
20
Order By: Relevance
“…This has been observed for ants, fl ies, ectoparasites of small mammals, and coral reef fi shes (Sale & Williams 1982, Gotelli & Ellison 2002, Rodriguez-Fernández et al 2006, Krasnov et al 2006. Moreover, Gotelli & McCabe (2002) observed that assembly rules cause matrix structuring according to the taxonomic group. Studies on larger scales usually do not agree with those obtained on smaller scales (Resetaris & Bernardo 1998), as observed for ant and fl y assemblages (Gotelli & Ellison 2002, Rodriguez-Fernández et al 2006.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been observed for ants, fl ies, ectoparasites of small mammals, and coral reef fi shes (Sale & Williams 1982, Gotelli & Ellison 2002, Rodriguez-Fernández et al 2006, Krasnov et al 2006. Moreover, Gotelli & McCabe (2002) observed that assembly rules cause matrix structuring according to the taxonomic group. Studies on larger scales usually do not agree with those obtained on smaller scales (Resetaris & Bernardo 1998), as observed for ant and fl y assemblages (Gotelli & Ellison 2002, Rodriguez-Fernández et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 96 presence/absence matrices, Gotelli & McCabe (2002) found signifi cant differences among taxonomic groups in the tested null models, with differences in the patterns of species distributions. According to the authors, most matrices were non-random among homeotherms when compared to poikilotherms.…”
mentioning
confidence: 96%
“…For example, investigating taxon occurrence patterns could provide signs of metabolic cooperation. Indeed, studies of both macroorganisms and microorganisms have indicated clear non-random distribution patterns [53,54]. However, as other factors, such as competition, niche (speciescomposition cycles and biogeography can be predicted from habitat parameters [55] or organismal physiological traits [56]) and sampling, might also contribute to the patterns observed, further studies will need to show what information can be extracted from such data.…”
Section: Metabolic Cooperationmentioning
confidence: 99%
“…As the existence of community structure is increasingly tested against the foil of null models and neutral theory (Hubbell 2001), it becomes more and more apparent that species are not ecologically equivalent and that niche differences, mediated by interspecific competition, create significant structure in ecological communities (Silvertown et al 1999;Gotelli & McCabe 2002;Clark & McLachlan 2003;Fargione et al 2003;McGill 2003;Adler 2004). Hence the question arises, how do the traits evolve on which niche differences are based and upon which community structure is built?…”
Section: Introductionmentioning
confidence: 99%